Sphaerosporella microspora (Pyronemataceae, Pezizales), a novel species from Southern China - Chen, Yan-Liu; Pan, Xue-Yu; Song, Jie; Liang, Jun-Feng (Phytotaxa, 2021)
Sphaerosporella microspora is described as a new species to science based on morphological and molecular data. It is characterized by its sessile apothecia, smooth hymenial surface, ectal excipulum composed of cylindrical and angular cells, subglobose to globose and smooth ascospores, and paraphyses without granules. A detailed description, color photographs of the fruiting bodies, line drawings of microstructures and a phylogenetic tree to show the placement of the new species are provided.